Social Capital, Civil Society and Democracy: The Case of Selected Malaysian Civil Society Organizations - Azeem Fazwan Ahmad Farouk (Kajian Malaysia, 2004)
The most recent variant of current democratic theory reveal an intense interest in the relationship between social capital and democracy. This theory posits that a vigorous associational life is beneficial for the creation and maintenance of democracy. This article challenges this conventional wisdom. Here, we argue that the existence of social capital per se may not bring about democratic consolidation. While we maintain that social networks are an important part of the social structure, democratic consolidation may only be attainable if social capital is converted into political capital.